1994
DOI: 10.1080/01688639408402695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self-generated cues in early Alzheimer's disease

Abstract: The ability to utilize cognitive support in the form of self-generated cues in mild Alzheimer's disease (AD), and the factors promoting efficient cue utilization in this group of patients, were examined in two experiments on memory for words. Results from both experiments showed that normal old adults as well as AD patients performed better with self-generated cues than with experimenter-provided cues, although the latter type of cues resulted in gains relative to free recall. The findings indicate no qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 38 publications
3
38
0
7
Order By: Relevance
“…Thus, despite extensive memory loss, reliable performance gains in explicit memory tasks can be demonstrated in early phase AD patients when extensive acquisition assistance is provided followed by strong support at retrieval. For instance, encoding can be enhanced through stimulus input that is multimodal (Lipinska and Ba Èckman, 1997), emotionally loaded (Moayeri et al, 2000), or through guidance to engage in self-generated semantic encoding (Lipinska et al, 1994) or in activation of task- (Arkin, 1992) or event-relevant prior knowledge (Johnson and Smith, 1998). Retrieval support may take the form of providing appropriate recall cues compatible with conditions at encoding (Bird and Kinsella, 1996).…”
Section: Facilitation Of Residual Explicit Memorymentioning
confidence: 98%
“…Thus, despite extensive memory loss, reliable performance gains in explicit memory tasks can be demonstrated in early phase AD patients when extensive acquisition assistance is provided followed by strong support at retrieval. For instance, encoding can be enhanced through stimulus input that is multimodal (Lipinska and Ba Èckman, 1997), emotionally loaded (Moayeri et al, 2000), or through guidance to engage in self-generated semantic encoding (Lipinska et al, 1994) or in activation of task- (Arkin, 1992) or event-relevant prior knowledge (Johnson and Smith, 1998). Retrieval support may take the form of providing appropriate recall cues compatible with conditions at encoding (Bird and Kinsella, 1996).…”
Section: Facilitation Of Residual Explicit Memorymentioning
confidence: 98%
“…In one single-case study, compared four specific errorless techniques and observed that those which were considered to demand more effort at encoding, requiring more active processing of the associations, were the most beneficial. Other studies have found that recall is facilitated by engaging in semantic elaboration at encoding (Lipinska & Bäckman, 1997), and that use of self-generated cues at encoding is more effective than use of experimenter-provided cues in assisting subsequent recall in AD (Lipinska, Bäckman, Mantyla, & Viitanen, 1994). Thus error elimination may not be the only important parameter when considering the efficacy of learning methods, and other issues, such as the cognitive effort involved in generating the target when learning, may also help to determine the efficiency of subsequent recall (Craik & Lockhart, 1972;Crutcher & Healy, 1989;Kolers & Roediger, 1984;McNamara & Healy, 1995;Squires et al, 1997;Tailby & Haslam, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…For example, the rather surprising fact that, in several cases, it was possible to teach patients to associate a self-generated thought (e.g, "where are my belongings", "what am I supposed to do today") with a behavioural action merits further laboratory research. It is already known from the list-learning literature that that self-generated cues are more effective than experimenter-provided ones in dementia (Lipinska, Bäckman, Mäntalyä, & Viitanen, 1994). An example of the potential for clinical research would be to determine the kinds of problem for which cognitive strategies such as those described in this paper may be appropriate, and those where they are likely to be useless.…”
Section: Resultsmentioning
confidence: 98%